Pension Wealth and the Timing of Retirement - Torben M. Andersen; Anne Katrine Borgbjerg; Jonas Maibom (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
We analyze how pension wealth influences retirement timing using 25 years of Danish administrative panel data on wealth and labor market status. Exploiting early-career variation in firm-specific mandatory pension contribution rates, we study labor supply decisions from age 55 onward. Greater pension wealth accelerates labor market exit: at age 63, the elasticity is about 0.3 — an additional 100,000 DKK (15,000 USD) at age 55 reduces earnings by 1% at age 63. Effects intensify near statutory retirement age, driven by self-support and early occupational pension withdrawals. Mandatory savings raise retirement wealth but induce earlier exit, underscoring key behavioral responses for pension policy design.
Keywords: J32; J26; J22; D14; 330; pension wealth; retirement; labor supply; mandated savings